Modification of atmospheric plasma jet system - Gary Schwartzenner Anak Gichai, author 611824; Norizah Redzuan, supervisor 250627; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper